INTEGRATED STRUCTURES OF ENGINEERING AND TECHNICAL RESOURCES TRAINING FOR INNOVATIONAL SECTORS OF REGIONAL ECONOMY - Andrey Yu. Aleksandrov; Victor A. Gartfelder; Vladimir G. Kovalev; A. . Sudlenkovaleksey (Высшее образование в России, 2016)
The article considers the issues of network cooperation between higher professional, secondary professional educational institutions and enterprises. Integrated structures appear to be an integral part of engineers’ training system in modern conditions. The educational scientific centre based on Chuvash State University and Electromechanical College is viewed as an example of such integrated structure focused on the development of highly technological production works.